Pengaruh Model Pembelajaran Science Environment Technology Society Terhadap Hasil Belajar Ilmu Pengetahuan Alam - sri sukmawati, ni made; citra wibawa, i made; aditya antara, putu (Universitas Pendidikan Ganesha, 2018)
The research was purpose to find out the differences on learning result of natural science between group of students who have been taught using learning model science environment technology society and groups of students who have been taught using conventional learning model. This research was study quasi-experiment, with non-equivalent postttest only control group design.Population of this research is all of class V SD in Gugus III Mendoyo Sub-district amounts to 129 person. The sample of this research were class V SDN 8 Penyaringan amounts to 21 personand SDN 1 Penyaringan amounts to 23 person. The sample was determined using random sampling technique. Learning result data was collected using multiple choice test. The data obtained were analyzed using descriptive statistical analysis technique and inferential statistical analysis (t-test). The results show that there are differences of result learning Inatural science between group of students who have been taught using learning model science environment technology society and groups of students who have been taught using conventional learning model class V SD in gugus III Mendoyo subdistrict.This is show by tcount (9,707)> ttable (2,000). Furthermore, the experimental group average (20.98) is greater than the control group mean (14.67). Thus, the science environment technology society learning model has a positive effect on the learning result of IPA in grade V SD students in Gugus III Mendoyo Subdistrict